Breaking Boundaries: The Success Story of Mathivathanan Tharmaluxmy, Founder of Luxmy Industry - Tharsika, K.; Priyanka, S. (University of Jaffna, 2024)
Introduction: Mathivathanan Tharmaluxmy, the founder of Luxmy Industry in Jaffna, is an innovative food artisan who has successfully established her business, challenging societal norms that traditionally confine women to domestic roles. Context and challenges: After the divorce, the founder encountered financial challenges along with societal and cultural expectations that discouraged her as a woman entrepreneur in the business world. In the early stages of her food and beverage venture, critical issues related to health and sustainability were overlooked, which negatively affected the business's initial success. Action Taken: Tharmaluxmy utilized innovative skills in food manufacturing, receiving support from a local women’s group and the Divisional Secretary. The Women Development Organization provided financial assistance to facilitate business growth, and a business loan was secured from BOC to further expand operations. During the initial phase, family members utilized social media to promote the business and distribute products locally at cultural events and exhibitions. Achievements: Luxmy industry has expanded from the domestic market into international markets, efficiently delivering goods to foreign customers through reliable courier services. The business prioritizes the employment of women, particularly those within the founder's family. Tharmaluxmy has received recognition for her achievements, including the prestigious Gamini Goriya Award for Best Woman Entrepreneur. Future Aspiration: The Export Development Board plans to showcase their products in Germany in February 2025. Additionally, a representative from the UK will visit her organization, as Tharmaluxmy intends to expand her operations into larger premises.
Keywords: Entrepreneur; Food; Innovative; Societal Norms